The Development of Learning Module in Social Knowledge on Economic Activity Based on Living Value Education of Responsibility Value - Heny Purnamasari; Asrori Asrori; Warneri Warneri (JETL (Journal of Education, Teaching and Learning), 2019)
This research intends to develop a learning media in the form of modules based on living values education, a module that develops key personal and social values, especially the value of responsibility, aimed at teaching students about the principle of responsibility, bringing students to be able to take responsibility for their behaviour and life. The research steps for developing the social studies learning module based on the living values education use the steps of the development of Borg and Gall, and the design of the learning model using the design of the Dick and Carey learning model. The steps of research and development start from: (1) studying various research findings related to devices that will be developed products, (2) developing the initial form of the device based on the research findings of living values education, (3) expert validation, (4) revising based on expert comments, (5) conducting a series of field tests (three experiments) on the place where the living values education module is used, and (4) revising the module to correct various weaknesses or errors found from the results of each field test. carried out by observation, interviews, and questionnaires, using research instruments in the form of observation guides, interview guides, and questionnaires. Data analysis used qualitative and quantitative analysis. The results showed that the design of the development of economic activity modules based on living values education consisted of (1) the stages of curriculum analysis and learning resources, (2) Analysis of student characteristics, (3) Analysis of tasks, (4) Analysis of material and concepts, (5) Formulate learning objectives, and (6) Planning phase. The development phase of the economic activity module based on living values education consists of: (1) Writing and compiling economic activity modules, (2) Expert assessment, (3) Module revisions based on expert comments, (4) Empirical trials, and (5) Module revisions based on trial comments. The implementation of learning using economic activity modules based on living values education begins with preparation, introduction, core activities, evaluating student work results, evaluation and closing. Obtaining student learning outcomes after using the module shows an increase, both from (1) aspects of knowledge, (2) aspects of attitude, and. (3) skill aspects, this means that economic activity modules based on living values education have effectiveness on the learning outcomes of VII grade MTs students. Al-Jihad in Pontianak City.